Graves' disease as an uncommon cause of acute pericarditis. (25th April 2014) - Kortekaas, Kirsten; van der Lienden, Bas; Jong, Simone; Riezebos, Robert
Abstract : Acute pericarditis is either dry, fibrinous or effusive, independent of its aetiology. A case is presented involving a 44-year-old man with acute pericarditis. The cause was established to be an aggravation of Graves' disease due to non-compliance with treatment. Pericarditis is an uncommon cardiac complication of Graves' disease and is associated with more recurrent episodes when not detected. Pharmacological treatment should include anti-inflammatory drugs in combination with treatment for hyperthyroidism. The specific pathophysiological link between the two conditions is still to be elucidated.